Chiral Separation of D,L-Mandelic Acid Using An Enantioselective Membrane Formed by Polycondensation of β-Cyclodextrin with 1,6-Diisocyanatohexane on A Polysulfone Membrane - Tian, Fei-Yu; Zhang, Jun- Hui; Duan, Ai-Hong; Wang, Bang-Jin; Yuan, Li-Ming (Journal of Membrane and Separation Technology, 2012)
An enantioselective composite membrane was prepared by polycondensation between β-cyclodextrin (β-CD) on a polysulfone support (PS) and a heptane solution of 1,6-diisocyanatohexane (1,6-DCH). The flux and permselective properties of the composite membrane were studied using an aqueous solution of D,L-mandelic acid as the feed solution. The influences of a number of parameters, such as the air-drying time of the β-CD solution on PS, the time of polymerization, the operating pressure and the feed concentration of the racemate, were studied. Chemical characterization was carried out using Fourier transform infrared spectroscopy and the top surface/cross-section was analyzed by scanning electron microscopy. The results showed that when using the enantioselective composite membrane for the optical resolution of the D,L-mandelic acid racemic mixture, an enantiomeric excess of over 85% could be obtained. The paper thus details, for the first time, how a poly(β-CD crosslinked with 1,6-DCH)/PS composite membrane can be used as an optical resolution membrane material to isolate the optical isomers of D,L-mandelic acid.